PENGARUH TAYANGAN TELEVISI FILM TERHADAP AHLAK BELAJAR ANAK - Edison Edison (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2018)
Television can easily devour most of the child's time spent in front of the television screen means that time is not used by children to learn to read, draw or help with housework. If television shows present entertainment programs or shows that are violent then children tend to like and like these shows because what they see, watching on television shows, usually children tend to imitate them without being filtered, filtered and without being selective. in choosing the program that is presented, so that it is afraid that it will damage the child's morals to the influence that is aired by television therefore the role of companion and guidance by parents to their children who are watching or enjoying shows that are served by television sets at home because every day many children - children spend time in front of the television set so that many shows or programs they enjoy without much thought about whether they are appropriate to watch by children - or can damage the morals of their children.